From Nationalization to Securitization: An Analysis of the Use of Genose Covid-19 Test Kits in Indonesia - Hakim, Fathoni (The Sunan Ampel Review of Political and Social Sciences, 2022)
This research was carried out starting from the contemplation of seeing the Indonesian Government Policy on handling COVID-19 which is often inconsistent in several ways. The consequence of these problems is the trend of an increase in the number of Indonesian people who were confirmed positive for COVID-19. One of the inconsistencies in Indonesian government Policy can be seen in using the GeNose C-19 as a legally used COVID-19 test kit in Indonesia. GeNose developed and produced by Gadjah Mada University is claimed to be the national product. The procedure of GeNose is different from Polymerase Chain Reaction (PCR) and Swab tests. GeNose uses a breathing technique, and its result can be seen in 80 seconds. Aside from that, GeNose is also relatively cheap in terms of cost, when compared to PCR tests and Swab tests. It was designated as an official COVID-19 test kit in early 2021 by the state and has officially started being used legally at various airports, stations, and bus terminals. But unfortunately, in the last few days, due to an increase in the number of Indonesians who are confirmed positive for COVID-19, GeNose has started to stop. Hence, this research will look at the dynamics of how the Indonesian government is carrying out the nationalization and securitization of the GeNose test kit The researcher uses Barry Buzan's securitization theory and public health policy approach as analytical tools. The research method used is a qualitative approach with content analysis techniques. The results of the study stated that the actor of the nationalization and securitization of the GeNose issue was the state. There is a shifting paradigm in threats from military security to human security. GeNose issue so that at first nationalized and then constructed into a security threat and carried out securitization.